Landslide Hazard Area Identification Using Smorph-Slope Morphology Method in Manado City - Erwin Hardika Putra (Jurnal Wasian, 2014)
Landsliding is one of the natural process that shape the earth’s surface to achieve slope stability and it will be hazard if they threat human life. This study was conducted to identify potential landslide hazard in Manado region using SMORPH method with digital elevation model (DEM) data. ASTER GDEM data provide more detail landslide information than SRTM data because of the higher spatial resolution. Result shows that 716 ha approximately of land have high landslide vulnerability and 1,176 ha approximately of land have medium landslide vulnerability.